The Development of Research-Based E-Booklet as Biotechnology Material Supplements to Improve Analytical Capabilities - Azizah, Nahirotul; Iswari, Retno Sri (FMIPA UNNES, 2021)
The background of the problem in this study is the analytical ability of students of SMA Negeri 13 Semarang on biotechnology material is still low. One of the consequences on the absorption of UN in 2017, 2018 and 2019 in the puspendik is also low. The teaching materials used are not yet in accordance with the needs and tastes of learners. in addition, learning is still focused on teachers with lecture and discussion methods. This, resulting in KD biotechnology has not been achieved. This research aims to develop research-based e-booklets on the application of conventional biotechnology as a supplement to biotechnology materials facilitated with learning devices. The research method used is Research and Development. Data collection in this study used interview guidelines, validation assessment sheet, clozure technique form, and response questionnaire. The results showed that based on expert assessment of materials and media on e-booklet developed showed very valid criteria with an average percentage of 92.77% and 93.4%. Trials of learners in the clozure technique got an average percentage of 96.33% with high criteria. Meanwhile, students and teachers' responses to e-booklets get an average percentage of 91.25% and 97.22% with very decent criteria. In the validation assessment, learning devices get very valid criteria on all devices created, including syllabus, RPP, LKPD, and evaluation questions with the average percentage obtained in a row is 87.76%; 90,04%; 92,01%; and 93.17%. Through learning using e-booklets that have been developed and refer to learning tools that have been created is expected to improve the analytical skills of learners.